2017
DOI: 10.1111/1467-9566.12543
|View full text |Cite
|
Sign up to set email alerts
|

Contract care in dentistry: sense‐making of the concept and in practice when multiple institutional logics are at play

Abstract: In 2009 contract dental care was introduced into Sweden's Public Dental Service under a programme called Dental Care for Health (DCH). Previous research has revealed a possible dilemma whereby dental care professionals had the role of insurance agent foisted upon them, as they were assigned the task of 'selling contracts'. Using qualitative interviews, this study explores how these professionals make sense of contract dental care today. Drawing on the concepts of occupational and organisational professionalism… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
1
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 23 publications
0
3
1
1
Order By: Relevance
“…It also indicated that the professionals responded to the request or expectation to sell in a strategic manner, by turning it into an element in their career advancement efforts. As such, the professionals' responses indicated an element of coping (Ulfsdotter Eriksson et al, 2017). However, coping did not quite capture what we saw in our data.…”
Section: Analysis Of Empirical Materialscontrasting
confidence: 80%
See 2 more Smart Citations
“…It also indicated that the professionals responded to the request or expectation to sell in a strategic manner, by turning it into an element in their career advancement efforts. As such, the professionals' responses indicated an element of coping (Ulfsdotter Eriksson et al, 2017). However, coping did not quite capture what we saw in our data.…”
Section: Analysis Of Empirical Materialscontrasting
confidence: 80%
“…In a broader scheme of things, we suggest that the relevance of strategic compliance might reach beyond the context of professional service firms. In particular, our findings might be relevant for the understanding of public service professionals, a context in which studies point to similar developments of commercialization and note that individual professionals need to navigate a general tension between organizational and occupational professionalism (Evetts, 2011;Noordegraaf, 2015;Taylor & Kelly, 2006;Ulfsdotter Eriksson et al, 2017). Strategic compliance offers a contribution to this literature by presenting a conceptualization of how professionals deal with this tension and how they navigate and respond to sales management in public organizations.…”
Section: Discussion and Concluding Remarksmentioning
confidence: 71%
See 1 more Smart Citation
“…The promotion of oral health and a good service level are still important in Sweden. [ 26 27 ] CDO's short-term aspirations and efforts were extremely concrete. Working and talking with their employees and “being seen” regularly in the workplace were key elements of their leadership.…”
Section: Discussionmentioning
confidence: 99%
“…Em razão da movimentada rotina clínica a que são submetidos os cirurgiões-dentistas, é indispensável a manutenção de toda a documentação referente ao atendimento executado nos pacientes, que se reveste de aspectos éticos e legais, já que tais registros constituem prova documental diante de pacientes insatisfeitos, que não hesitam em recorrer aos Conselhos Regionais de Odontologia ou até mesmo à justiça, devido à intensa atuação da mídia, que tem dedicado grande espaço ao chamado "erro médico" 30 , após a promulgação do Código de Defesa do Consumidor, que se caracteriza pelo exacerbado protecionismo ao consumidor -neste caso, o paciente -, que supostamente se apresenta como frágil, por não possuir um grau de conhecimento sobre o serviço que lhe está sendo fornecido 31 .…”
Section: Procedimento Odontológicounclassified